The effects of climate change on fungal diseases with cutaneous manifestations: A report from the International Society of Dermatology Climate Change Committee - Aditi Gadre; Wendemagegn Enbiale; Louise K Andersen; Sarah J Coates (Elsevier, 2022)
Climate change affects all aspects of ecosystems, including humans and numerous microorganisms. Fungi are especially sensitive to climate extremes. Persistently warmer temperatures at increasingly higher latitudes are contributing to ongoing expansion of the geographic ranges of known fungal pathogens. Alongside fungal species' advancement into new territories, many have the capacity to develop thermotolerance. Consequently, a greater number of previously unharmful or underappreciated fungal species may emerge due to climate change.More frequent extreme weather events - including heat waves, drought, and flooding - also foster circumstances that favor the survival and infectivity of pathogens. We reviewed the English language literature in order to describe what is known about the effects of climate change on fungal infections with cutaneous manifestations. We included candidal infections, dermatophytoses, other mold infections, and deep fungal infections, and focused on organisms with evidence of climate sensitivity, particularly those that are emerging, spreading to new geographic regions, or both. This may provide an important tool for understanding the epidemiological patterns underlying fungal transmission, predicting future outbreaks, and adopting effective control strategies.